Gender and Sexual Dimorphism in Flowering Plants 1999
DOI: 10.1007/978-3-662-03908-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism and Biotic Interactions

Abstract: In the last decade, an increasing number of studies have suggested that males and females of dioecious plants may be differentially affected by competition, herbivory, and parasitism. In dioecious plant species, there is a fundamental sexual difference in patterns of reproductive allocation. Males may allocate more resources to reproduction than females during flowering, but total reproductive allocation is typically greater in females than in males (Chap. 6). These sexual differences in schedules of reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
3
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 113 publications
(139 reference statements)
7
121
3
2
Order By: Relevance
“…This suggest that the explanation for the changes is more complicated than simple flow-on effects into the secondary metabolism Despite the well-documented high degree of selectivity of bank voles (e.g. Hansson 1985;Danell et al 1991;HjältØn et al 1996;gren et al 1999;Pusenius 2001;Hallgren & HjältØn 2002) and higher concentration of condensed tannins in line SPS33A and (marginally) SPS26 we found no significant difference in vole preference for the GM poplars and the wild-type. Hallgren & HjältØn (2004) found strong indications that condensed tannins have a negative effect of plant palatability to bank voles.…”
Section: Discussioncontrasting
confidence: 44%
“…This suggest that the explanation for the changes is more complicated than simple flow-on effects into the secondary metabolism Despite the well-documented high degree of selectivity of bank voles (e.g. Hansson 1985;Danell et al 1991;HjältØn et al 1996;gren et al 1999;Pusenius 2001;Hallgren & HjältØn 2002) and higher concentration of condensed tannins in line SPS33A and (marginally) SPS26 we found no significant difference in vole preference for the GM poplars and the wild-type. Hallgren & HjältØn (2004) found strong indications that condensed tannins have a negative effect of plant palatability to bank voles.…”
Section: Discussioncontrasting
confidence: 44%
“…Although comparing male and female traits through all the stages of a species' life-history is critical to understanding the ecology and evolution of dioecious species (Lloyd and Webb 1977;Shine 1989), there is little information on the timing of onset of sex-specific differences in non-morphological traits in dioecious plant species (Dawson and Geber 1999;Å gren et al 1999). The primary reason for the lack of knowledge in this area is that determining the gender of sexually immature individuals using morphology only is impossible for most dioecious plant species (Dawson and Geber 1999).…”
Section: Gender-specific Differences In Competitive Effectmentioning
confidence: 99%
“…The first review of the empirical studies on the topic of sex-biased herbivory concluded that “males are more likely than females to be preferentially used by herbivores” and suggested that male-biased herbivory was widespread among dioecious species [72]. The authors, however, recognized that sex-biased herbivory was by no means a unanimous finding across all the dioecious species examined to that date, and that the relative susceptibility of each sex to herbivory could be influenced, among other factors, by fluctuations in ecological tradeoffs between functions (rather than evolutionary changes in patterns of allocation), such as phenological changes in resource allocation to reproduction and growth [75, 89].…”
Section: Introductionmentioning
confidence: 99%